Aboodh Transform Iterative Method for Spatial Diffusion of a Biological Population with Fractional-Order - Ojo, Gbenga O.; Mahmudov, Nazim I. (Mdpi, 2021)
In this paper, a new approximate analytical method is proposed for solving the fractional biological population model, the fractional derivative is described in the Caputo sense. This method is based upon the Aboodh transform method and the new iterative method, the Aboodh transform is a modification of the Laplace transform. Illustrative cases are considered and the comparison between exact solutions and numerical solutions are considered for different values of alpha. Furthermore, the surface plots are provided in order to understand the effect of the fractional order. The advantage of this method is that it is efficient, precise, and easy to implement with less computational effort.
Keywords: biological model; fractional derivative; partial differential equation; Aboodh transform; iterative method